2020
DOI: 10.1038/s41598-020-61504-2
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological responses to images ranging in motivational salience: Attentional abnormalities associated with schizophrenia-spectrum disorder risk

Abstract: current study. We further explore whether there were earlier selective attention abnormalities in at-risk groups, evidenced by deviant EPN amplitudes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 82 publications
4
10
0
Order By: Relevance
“…An additional and complementary explanation of that effect may refer to the degree or the magnitude of the saliency features of the presented faces and, therefore, to the specificity of these saliency effects. Both analysed ERP components are modulated by the saliency of stimuli (P3— Teixiero et al., 2010 ; LPP— Martin et al. , 2020 ) and thus, substantially increased P3 and LPP amplitudes to the self-face may reflect the extreme saliency of this stimulus, in line with other studies ( Humphreys and Sui, 2015 ).…”
Section: Discussionsupporting
confidence: 87%
“…An additional and complementary explanation of that effect may refer to the degree or the magnitude of the saliency features of the presented faces and, therefore, to the specificity of these saliency effects. Both analysed ERP components are modulated by the saliency of stimuli (P3— Teixiero et al., 2010 ; LPP— Martin et al. , 2020 ) and thus, substantially increased P3 and LPP amplitudes to the self-face may reflect the extreme saliency of this stimulus, in line with other studies ( Humphreys and Sui, 2015 ).…”
Section: Discussionsupporting
confidence: 87%
“…The findings of decreased implicit positive affect in SocAnh are consistent with some other findings suggesting SocAnh is associated with decreased responses in other positive affect measures. For instance, in an ERP study that examined the late positive potential (LPP), there was evidence of a decreased early response to positive stimuli in SocAnh, with SocAnh also associated with a relatively smaller LPP for positive than for negative stimuli (Martin et al, 2017, 2019). In another study that employed a linguistic analysis of a free writing period, SocAnh was associated with decreased used of positive words, even after a positive mood induction (Fung et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Power analysis indicated that a sample size of 25 participants per group was sufficient to test the primary hypothesis of the current study (see Supplementary Materials for more details). Further details on screening and recruitment are available in Martin, Li, and Castro (2020). 1 Eight participants were excluded due to equipment failure (n = 2, one from each group) and low reliability of their CNV, defined as having fewer trials than needed to achieve a dependability point estimate of 0.7 (n = 6, three from each group).…”
Section: Participants and Measuresmentioning
confidence: 99%
“…They were not included in the current analysis due to low reliability of their CNV. Specifically, 190 trials were needed to achieve a dependability point estimate of 0.7 for participants with elevated social anhedonia, which exceeds the total number of trials.2 To minimize participant burden, they only rated a random subset of 30 images previously viewed from the serial instrumental learning task and from another, unrelated task reported inMartin et al (2020).Cogn Affect Behav Neurosci (2020) 20:873-887…”
mentioning
confidence: 99%